A Comprehensive Review of Fingerprint Recognition Systems, Methods, and Algorithms - Sharma, Himanshi; Singh, Hardeep (International Journal of Computer Sciences and Engineering, 2025)
Today, we need security in every system, be it our personal laptop, computer system, ATM system, etc. We need to ensure that our data is well protected from misuse by imposters by verifying the identity of a user. Traditional systems of verification using credentials are not foolproof and face many challenges. These systems cannot meet the growing security demands in applications such as border crossing. Therefore, biometric recognition is becoming popular day by day. Biometrics is a way of verifying a user’s identity using innate traits that define the individual. This work gives a review of biometrics, particularly fingerprint recognition systems. The study also assesses popular methods, including the Bozorth3 algorithm, Otsu’s Thresholding, Gabor Filters, and Global Threshold Segmentation. There is a discussion of comparative insights into their limitations and performance. In addition to providing a comprehensive literature review, this paper identifies current research gaps and suggests potential directions for future advancements in fingerprint recognition technology.